Pengaruh Motivasi Kualitas Dan Pengetahuan Perpajakan Terhadap Minat Mahasiswa Akuntansi Dalam Mengikuti Brevet Pajak Di Moderasi Oleh Motivasi Ekonomi - Adinda Suci Ramadhini; Uum Helmina Chaerunisak (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to prove the effect of quality motivation and knowledge of taxation on the interest of accounting students in participating in tax brevet which is moderated by economic motivation. This research is a quantitative research with the interest of accounting students in following the tax brevet as the dependent variable. The sample of this study was students of the 2018-2021 accounting study program, Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sample was selected by purposive sampling method with certain criteria. The total sample is 88 students who have been calculated by the slovin formula. Data analysis was performed using multiple linear regression analysis and moderate regression analysis (MRA) with SPSS version 25. The results of this study indicate that quality motivation has a positive effect on the interest of accounting students in taking tax brevet, knowledge of taxation has a positive effect on the interest of accounting students in taking tax brevet, economic motivation strengthens the positive influence of quality motivation on accounting students' interest in taking tax brevet, and economic motivation strengthens positive effect of tax knowledge on accounting students' interest in participating in tax brevet. Keywords: Quality Motivation, Tax Knowledge, Interest of Accounting Students in Following Tax Brevet, and Economic Motivation.